Green Accounting and Institutional Ownership Patterns in Healthcare Firm Profitability: Akuntansi Hijau dan Pola Kepemilikan Institusional dalam Kinerja Keuntungan Perusahaan Kesehatan - Hariyanto, Wiwit; Syukriyah, Ziyadatus (Indonesian Journal of Law and Economics Review, 2026)
General Background: The healthcare sector has experienced rapid growth alongside increasing demands for corporate accountability toward environmental and social responsibilities. Specific Background: Companies are encouraged to adopt Green Accounting practices and strengthen institutional ownership as governance mechanisms to maintain legitimacy and transparency. Knowledge Gap: Prior studies mostly focus on banking or general industries, while limited empirical evidence examines how these mechanisms relate to profitability in healthcare firms. Aims: This study analyzes the relationship between Green Accounting and institutional ownership with profitability of healthcare companies listed on the Indonesia Stock Exchange during 2020–2024. Results: Using purposive sampling of 31 firms and multiple linear regression on 109 observations, the findings show that Green Accounting does not show a significant relationship with profitability, while institutional ownership demonstrates a negative association, and both variables explain only 8.4 percent of profitability variation. Novelty: The research concentrates on the healthcare sector and applies environmental cost indicators to represent Green Accounting within this context. Implications: The results indicate that governance and environmental reporting alone are insufficient to explain financial outcomes, suggesting the need for broader managerial and operational factors in improving firm profitability. Keywords: Green Accounting, Institutional Ownership, Profitability, Healthcare Sector, Financial Performance Key Findings Highlights: Environmental cost allocation shows no measurable linkage with earnings ratio Higher institutional shareholding corresponds to short-term margin decline Explanatory power of the model remains limited at 8.4 percent